Currency Futures and Currency Crises - Andreas Röthig (Technische Universität Darmstadt, Department of Law and Economics, 2004)
Since financial derivatives are key instruments for risk taking as well as risk reduction, it is only straightforward to examine their role in currency crises. This paper addresses this issue by investigating the impact of currency futures trading on the underlying exchange rates. After a discussion of trading mechanisms and trader types, the linkage between futures trading activity and spot market turbulence is modelled using a VAR-GARCH approach for the exchange rates of Australia, Canada, Japan, Korea and Switzerland in terms of the US dollar. The empirical results indicate that there is a positive relationship between currency futures trading activity and spot volatility. Moreover, in the case of four out of the total of five currencies discussed in this paper, futures trading activity adds significantly to spot volatility.
Keywords: C32; C13; F31; G15; 330; Currency crises; Exchange rate volatility; Currency futures trading activity; VAR-GARCH estimation; Devisentermingeschäft; Wechselkurs; Volatilität; Währungskrise; Devisenspekulation; Schätzung; Südkorea; Australien; Kanada; Japan; Schweiz